Perencanaan Sistem Kelistrikan Gedung Kantor Pertanahan Kabupaten Bolaang Mongondow Utara - Humena, Steven; Mohamad Andriansyah Posumah; Frengki Eka Putra Surusa; Adnan Qosim; Rahmad Hidayat Boli (Department of Electrical Engineering, UNJANI, 2024)
Office buildings and homes are in dire need of electrical installations, but there are still quite a lot of people we meet who do not understand the design of safe electrical installations in accordance with the General Regulation on Electrical Installation (PUIL). By paying attention to PUIL in the installation of electrical installation design, a good and correct and safe electrical installation can be obtained. The purpose of this study is to determine a good and correct and safe electrical installation, determine the specifications and safety components needed and determine the recapitulation of the power used. The method of planning the electrical system in the building follows the standards that have been determined, namely PUIL 2020 and SNI energy conservation in lighting systems 2020. This planning produces installation design drawings in the form of situation drawings and one-line diagrams. From the calculation, a current of 55.63 Amperes was obtained and a total installed power of 36,571 VA, so that the main MCCB protection component was selected with a capacity of 3 x 63 Ampers. For the submission of electrical power connection services to PT. PLN (Persero) is 41,500 VA with a 3 x 25 Ampere MCB limiter. The type and cross-sectional area of the cable selected for the main cable based on PUIL 2020 is NYY 4 x 25 mm2.